'Face'-related expressions in the Minnan Dialect of Chinese. (November 2022) - Chen, Jiejun; Kádár, Dániel Z.; House, Juliane
Abstract: In this study, we investigate the use of 'face'-related expressions in the Minnan Dialect of Chinese. Minnan is often referred to as a 'conservative' dialect because of its large inventory of archaic and local expressions, including a rich variety of 'face'-related expressions. To date, little research has been dedicated to this 'face'-related inventory in Minnan, supposedly because it is often assumed that 'face' is a homogeneous notion in Chinese. In this paper, we critically revisit this assumption. In our study, we first collected and categorised Minnan dialectal 'face'-related expressions and their use with the aid of data drawn from audio-recorded conversations, online videos, dictionaries, literary works and interviews. The results pointed to significant differences between Minnan 'face'-expressions and their Mandarin counterparts. We then distributed a test to two groups of speakers: speakers of Mandarin who were not fluent in Minnan and a group of Minnan speakers. The aim of this test was to find out whether both groups can interpret Minnan 'face'-related expressions in a written form. We hypothesised that Minnan 'face'-related expressions in a written form can easily be interpreted by Mandarin speakers because Mandarin and Minnan use roughly the same writing system. However, this hypothesis was falsified because a significant number of Minnan 'face'-related expressions triggered various types of interpretational difficulties for Mandarin-speakers for various reasons. This outcome indicates that Minnan 'face'-related expressions should be studied as a repertoire, which is different from but related to Mandarin. Highlights: Provides new insights into 'face' in Chinese by exploring 'face'-related expressions in the Minnan Dialect. Proposes a mixed-method approach to the study of 'face'-related expressions. Demonstrates that it is problematic to make  a priori  assumptions about 'face' in Chinese based on Mandarin only.